1976
DOI: 10.1136/jcp.29.suppl_10.35
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation disorders

Abstract: The risk of severe haemorrhage in pregnancy is well recognized, and uncontrolled bleeding remains a major cause of maternal death throughout the world, including the British Isles. The haemochorial system of human placentation carries with it an inherent risk of haemorrhage and this probably explains why the serious congenital disorders of haemostasis are predominantly found in the male. In pregnancy, complex physiological changes occur in the systems responsible for the control of blood loss from the vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…14 Weenink et al, 24 using the chromogenic substrate (S 2238) assay we used in this study, found no significant variation in the antithrombin III concentration throughout pregnancy and Puerperium compared to nonpregnant levels. A similar conclusion was reported more recently by Stirling et al 14 Our finding of a slight but statistically significant decrease in antithrombin III levels in the second and third trimesters of pregnancy confirms other reports 22,25 and could be other indirect evidence of thrombin generation. Reports on platelet count in pregnancy have provided discordant results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…14 Weenink et al, 24 using the chromogenic substrate (S 2238) assay we used in this study, found no significant variation in the antithrombin III concentration throughout pregnancy and Puerperium compared to nonpregnant levels. A similar conclusion was reported more recently by Stirling et al 14 Our finding of a slight but statistically significant decrease in antithrombin III levels in the second and third trimesters of pregnancy confirms other reports 22,25 and could be other indirect evidence of thrombin generation. Reports on platelet count in pregnancy have provided discordant results.…”
Section: Discussionsupporting
confidence: 81%
“…11,15,[17][18][19][20][21] In the present study, the vWFAg/VIII:C ratios in the first, second, and third trimesters are 1.23, 1.7, and 1.6, respectively. Such elevated ratios are common in normal pregnancy 14,22,23 and are indicative of thrombin-induced loss of factor VIII:C activity as a consequence of activation of the coagulation system and thrombin generation. 14 Weenink et al, 24 using the chromogenic substrate (S 2238) assay we used in this study, found no significant variation in the antithrombin III concentration throughout pregnancy and Puerperium compared to nonpregnant levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is a decrease in the spontaneous fibrinolytic activity and of the vein wall activator activity (6,21). During parturition and placental separation there are changes indicative of activation and consumption of coagulation factors (5,20). A normalization of the low spontaneous fibrinolytic activity and the low vein wall activator activity found during pregnancy takes place almost immediately after placental separation (20, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Oral anticoagulants are contraindicated because they cross the placenta and may cause fetal abnormalities and death (1 -3 ). Unfractionated heparin (U F -H ) does not cross into the fetal circulation (4,5) and is the anticoagulant o f choice during pregnancy. L ow molecular weight heparins (L M W -H ) present some advantages over U F-H : Their absorption after s. c. administration is more complete and anti-Xa activity is maintained for a longer time (6 -8 ).…”
Section: Introductionmentioning
confidence: 99%